Pembelajaran Bahasa Inggris Menyenangkan untuk Anak Sekolah Dasar melalui Program PKM di Taman Sari Hijau - Leil Badrah Zaki; Theodesia Lady Pratiwi; Pandu Prasodjo; Nurlaily; Tetti; David Sutan; Hardy Christ; Nifaila Najwa Inayah; Olivia Museng (STMIK Royal, 2026)
Abstract: The purpose of this service program (PKM) that we have held in Taman Sari Hijau Housing aims to study the extent of the ability or competence of elementary school children in English in the housing. With a quota of 30 students, we came to the conclusion that most of the students, apart from the lack of access to English content, we also found a lack of interest in English, so the PKM that we conducted was not only about studying partner problems, but also introducing them to English and teaching with more effective methods, and the results showed that children do need a more